Languages for Specific Purposes in the Business Services Sector in Poland 2021. Origins, Background, Results and Perspectives of the Language Barometer of Lódź - Grzeszczakowska-Pawlikowska, Beata; Makowski, Jacek; Stawikowska-Marcinkowska, Agnieszka (2022)
The core of this article as a contribution to the current discourse on the opportunities, challenges and limits for foreign and specialised language didactics of closer cooperation of Universities with the economic and social environment, is the presentation and discussion of the background, origins, results and perspectives of the research project “The Language Barometer of Lodz 2021. Employees of the modern business services sector”. The research questions of the survey are primarily directed at the required foreign language skills of the target group, areas of application of foreign languages, the knowledge and specialist areas to be mastered, language training in the company, as well as the aspect of multilingualism in the context of realised professional communication. The paper will present and discuss the global results of the survey, and also provide a full package of anonymous raw data collected during the survey for possible further analysis and study. The data obtained in the survey can be used for projects and research initiatives on various aspects of specialised communication in an intercultural work environment, but also find application in, among other things, the development or modification of curricula at different levels of learning, the creation of specialisation modules, language courses, workshops or educational materials.
Keywords: Languages for Specific Purposes; LSP; Business Services; Professional Communication; German; Multilingualism